Konsep Dasar Ilmu (Kajian Dalam Filsafat Yunani, Filsafat Islam, Dan Filsafat Modern) - Moch. Khafidz Fuad Raya (FALASIFA : Jurnal Studi Keislaman, 2016)
Speaking of science, the science is endless to be discussed, because it is the principal basis of the times. A civilization is formed in a contribution that science continues to evolve. Theoretical and empirical studies in the science of generating scientific method. Provides basic theoretical study and / or kerangak think that generate hypotheses, while empirical studies are testing hiptesis digging through the facts on the ground as a basis for conclusions. The paradigm then generate knowledge, and the emergence of a disciplines such as science, social sciences and humanities, resulting from the expansion of the perspective and discussion of the highly evolved of the meaning of science itself. The basic concept of the science of obtaining a special discussion, so that in the realm of philosophy into a discourse in shaping the basic concepts of the disciplines of birth. The development of the basic concepts of science has expanded in several studies of philosophy, both in philosophy western world (Greece), medieval philosophy (Islamic philosophy), and modern philosophy. So great was the role of science in the development of the age and the progress of civilization. So in this paper will discuss how the basic concepts of science in terms of philosophy, both in terms of Greek philosophy, medieval philosophy (Islamic philosophy), and modern philosophy, so it will obtain a comprehensive discussion related to the basic concepts of science. Â Keywords: science, basic concepts, philosophy